ELECTION SPENDING AND ITS SOCIO-ECONOMIC DETERMINANTS: EFFECTS ON TOTAL DEPOSITS IN GHANA - Ofori, Kofi Samuel; Asante , Ama Elizabeth; Antwi , Kwame Michael (International Journal of Allied Research in Economics (IJARE), 2024)
Developing nations have been experiencing lower savings rates compared to East Asia and other developed regions over the past decade. Sub-Saharan Africa and Latin America have seen a drastic reduction in savings during the same period. Savings, defined as the sacrifice of current consumption for future benefit, play a crucial role in the accumulation of capital, which in turn can lead to increased future output and consumption. The significance of savings for domestic capital accumulation in developing countries has been a central topic in economics, finance, and development literature, from classical economic theories to the Harrod-Domar and Solow models of economic growth. Recently, savings have gained increased attention due to threats of expropriation, repudiation, and other hostile actions against foreign capital suppliers, as well as decreasing donor assistance. Savings contribute to income growth, increased consumption, and the smoothening of consumption amidst various uncertainties. This paper examines the effects of selected socio-economic factors and election spending on aggregate savings (total deposits) in Ghana. By analyzing data over a specified period, the study aims to understand the dynamic relationship between socio-economic variables, political expenditures, and savings behavior in the Ghanaian context. The findings will provide insights into policy measures that can enhance savings rates and support economic development in Ghana.